Institutions in international relations : understanding the effects of the GATT and the WTO on world trade - Goldstein, Judith (2007)
Evaluates the effects of the GATT/WTO and other trade agreements since World War II. Organizes the analysis around two factors viz. institutional standing and institutional embeddedness. Shows that many countries had rights and obligations, or institutional standing, in the GATT/WTO even though they were not formal members of the agreement. Expands the analysis to include a range of other commercial agreements that were embedded with the GATT/WTO.